Microwave-assisted organic syntheses: microwave effect on intramolecular reactions – the Claisen rearrangement of allylphenyl ether and 1-allyloxy-4-methoxybenzene. Issue 110 (22nd October 2015) - Horikoshi, Satoshi; Watanabe, Tomoki; Kamata, Momoko; Suzuki, Yumiko; Serpone, Nick
Abstract : We examined the possible effect microwaves may have on intramolecular reactions such as the Claisen-type rearrangement process carried out in DMSO solvent and in solvent-free microwave irradiation conditions. Abstract : This article examined how and the possible effect microwaves may have on intramolecular reactions such as those of the Claisen-type rearrangement carried out in dimethyl sulfoxide (DMSO) solvent and in solvent-free, microwave irradiation conditions. For comparison, the reaction was also performed by conventional heating using an oil bath. 2-Allylphenol was synthesized from allylphenyl ether in DMSO solvent under stirring conditions as a model intramolecular reaction taking place via the Claisen rearrangement using a commercial microwave chemical apparatus together with conventional heating; no enhancement of the reaction occurred. To further examine the influence of microwave irradiation on Claisen rearrangement reactions, we also investigated the transformation of 1-allyloxy-4-methoxybenzene to 2-allyl-4-methoxyphenol under both solvent-free conditions (no stirring) and in DMSO medium; here also no reaction enhancement was observed. This notwithstanding, microwaves did impact the formation of a by-product formed in the latter reaction, which was identified by GC and GC/MS as 4-methoxyphenol, the yield of which was nearly fourfold greater ( ca. 6%) under microwave irradiation than under oil-bath heating ( ca. 1.5%). The latter suggests that under solvent-free conditions a microwave non-thermal effect influenced the formation of this by-product during the Claisen rearrangement process, contrary to the case where the reaction was performed in DMSO medium for which the yields were identical ( ca. 2.5%), regardless of whether the reactant was microwave or oil-bath heated.